Femoral neck system vs. cannulated screws on treating femoral neck fracture: a meta-analysis and system review - Zhou, Yimin; Li, Zongyang; Lao, Kecheng; Wang, Zixiu; Zhang, Li; Dai, Shiyou; Fan, Xiao (Frontiers in Surgery, 2023)
Objective： This meta-analysis aimed to assess the relative safety and efficacy of cannulated compression screw (CCS) and Femoral Neck System (FNS) in the treatment of patients with femoral neck fractures and to provide evidence-based medical evidence for FNS in the treatment of femoral neck fractures. Methods： Pubmed, EMBASE, Cochrane, and CNKI databases were searched to collect outcomes following FNS and CCS for femoral neck fractures. Meta-analysis was performed using RevManv5.4 (The Cochrane Collaboration) and Stata v14.0 software. Results： This analysis included 21 studies involving 1347 patients. The results showed that FNS was superior to CCS in terms of fracture healing time (MD = -0.75, 95% CI = [-1.04 to -0.46], P<0.05), the incidence of bone nonunion (OR = 0.53, 95% CI = [0.29 to 0.98], P=0.04), the incidence of osteonecrosis of the femoral head (OR = 0.49, 95% CI = [0.28 to 0.86], P=0.01), the incidence of internal fixation failure (OR = 0.30, 95% CI = [ 0.18, 0.52], P <0.05), femoral neck shortening rate (OR = 0.38, 95% CI = 0.27, 0.54, P>0.05), Harris hip score (MD = 3.31, 95% CI = [1.99 to 4.63], P<0.001), Barthel index (MD = 4.31, 95% CI = [3.02 to 5.61], P<0.05), intraoperative bleeding (MD = 14.72, 95% CI = [ 8.52, 20.92], P<0.05), fluoroscopy frequency (OR = 0.53, 95% CI = [0.29, 0.98], P=0.04) and complications (OR = 0.31, 95% CI = [0.22, 0.45],P<0.05). The difference between FNS and CCS in operative time was not statistically significant (MD = -2.41, 95% CI = [-6.88 to 2.05], P=0.29). Conclusion： FNS treatment of femoral neck fracture can shorten the healing time of fracture, reduce the incidence and translucent rate of bone nonunion, osteonecrosis of the femoral head and internal fixation failure, reduce intraoperative blood loss and postoperative complications, and improve hip joint function and activity. We are confident in the findings that FNS, an effective and safe procedure for internal fixation of femoral neck fractures, is superior to CCS.